Corporate Equality and Equity Prices: Doing Well While Doing Good? - Shihe Fu; Liwei Shan (Economics and Econometrics Research Institute (EERI), 2009)
Two competing hypotheses, value enhancing and value discounting, state that implementing socially responsible corporate policies can have positive or negative effects on firm value. This paper tests how a specific type of social responsibility–corporate equality–affects firm value. Corporate equality is measured by the corporate equality index (CEI). This index quantifies how companies treat their gay, lesbian, bisexual, and transgender employees, consumers, and investors. Using a sample of CEI-rated, publicly traded firms in the U.S., we find that, between 2002 and 2006, firms with a higher degree of corporate equality have higher stock returns and higher market valuation (Q). We provide suggestive, causal evidence that corporate equality enhances firm value through better performance in product markets and labor markets: Firms with a higher degree of corporate equality also tend to have larger sales, higher profit margins, higher employee productivity, and attract more employees. These results are robust to the inclusion of unobserved firm-heterogeneities. Overall, our results support the value-enhancing effects of corporate social responsibility.
Keywords: G11; G12; J70; M14; 330; Corporate equality; social responsibility; socially responsible investment; stock returns; performance